Titanium cobalt doped m-type strontium ferrite wave-absorbing material and preparation method thereof

By co-doping M-type strontium ferrite with Ti4+ and Co2+ ions, the problem of unsatisfactory microwave absorption performance of M-type strontium ferrite materials in a wide frequency band was solved, realizing the preparation of high-efficiency microwave absorbing materials with low cost and large-scale production, thus broadening the effective absorption bandwidth and reducing production costs.

CN123026438APending Publication Date: 2026-11-03TONGLING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320419.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-11-03

Smart Images

  • Figure CN123026438A_ABST
    Figure CN123026438A_ABST
Patent Text Reader

Abstract

The application provides a titanium-cobalt-doped M-type strontium ferrite wave-absorbing material and a preparation method thereof, and relates to the technical field of wave-absorbing material design. 11‑2x Ti x Co x O 19 , wherein the value range of x is 0.3-0.9. The application overcomes the defects of the prior art, and through the co-doping substitution of Ti 4+ and Co 2+ ions to Fe 3+ ions, the magnetic crystal anisotropy and electromagnetic parameters of the material are regulated, the impedance matching characteristics are improved, the effective absorption bandwidth is significantly widened, the wave-absorbing intensity is enhanced, and meanwhile, the solid-phase reaction method with simple process is adopted, so that the low-cost and large-scale production is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microwave absorbing material design technology, specifically to a titanium-cobalt doped M-type strontium ferrite microwave absorbing material and its preparation method. Background Technology

[0002] M-type strontium ferrite (SrFe) 12 O 19 Strontium ferrite (SFR) is a typical hexagonal hard magnetic ferrite material with high magnetocrystalline anisotropy, good chemical stability, and low cost. It is not prone to skin current at high frequencies, has a low dielectric constant, and can be mixed with other absorbing materials, showing broad application prospects in the field of electromagnetic wave absorption. However, in the frequency range of 2–18 GHz, SFR prepared by traditional methods has low density, as well as low dielectric and magnetic losses, resulting in less than ideal absorption performance.

[0003] To improve the microwave absorption properties of M-type strontium ferrite, ion doping modification is currently the main method. This involves introducing transition metal ions or rare earth ions into the strontium ferrite lattice to replace Sr. 2+ position or Fe 3+ By controlling the magnetocrystalline anisotropy, saturation magnetization, coercivity, and other magnetic properties of the material, as well as its dielectric properties, impedance matching characteristics can be improved and microwave absorption performance can be enhanced.

[0004] The existing technology still has the following shortcomings: (1) Insufficient absorption performance: The pure phase M-type strontium ferrite prepared by traditional methods has low dielectric loss and magnetic loss in the frequency range of 2 to 18 GHz, and the absorption performance is not ideal. Even the strontium ferrite prepared by the sol-gel method is difficult to obtain an effective absorption bandwidth (RL≤-10dB) with a thin matching thickness, and the effective absorption bandwidth is only about 1 GHz with a certain matching thickness. (2) Narrow effective absorption bandwidth: Although the existing doping modification scheme has improved the absorption performance to a certain extent, the effective absorption bandwidth is generally narrow, which is difficult to meet the application requirements of "wide bandwidth and strong absorption". For example, the effective absorption bandwidth of some doped systems only covers a specific narrow band and cannot achieve wide band coverage. (3) Complex preparation process: In the existing technology, wet chemical preparation processes such as sol-gel method and hydrothermal method involve complex processes such as sol preparation, pH adjustment, long-term gelation, and multi-step heat treatment. The process is long, the operation is cumbersome, and the cycle is long, which is not conducive to large-scale industrial production. (4) High cost of doping elements: Some doping systems use rare earth elements (such as Nd, Gd, Pr, La, Ce, etc.), which are expensive and increase the cost of material preparation, which is not conducive to large-scale promotion and application. (5) Unsystematic research on doping systems: Existing research on Ti-Co co-doped strontium ferrites mainly focuses on magnetic property control, and there is a lack of systematic research on its absorption performance in the 1-18 GHz wide frequency range. In particular, the influence of doping amount on electromagnetic parameters and absorption performance has not been fully revealed. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a titanium-cobalt-doped M-type strontium ferrite microwave absorbing material and its preparation method, using Ti... 4+ and Co 2+ ion pairs Fe 3+ Ion co-doping substitution modulates the magnetocrystalline anisotropy and electromagnetic parameters of the material, improves impedance matching characteristics, significantly broadens the effective absorption bandwidth, and enhances the absorption intensity. At the same time, the simple solid-state reaction method enables low-cost, large-scale production.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A titanium-cobalt-doped M-type strontium ferrite microwave absorbing material, wherein the general chemical formula of the microwave absorbing material is SrFe 11- 2x Ti x Co x O 19 , where x takes values ​​ranging from 0.3 to 0.9.

[0007] Preferably, the value of x is any one of 0.3, 0.6 or 0.9.

[0008] The preparation method of the above-mentioned microwave absorbing material includes the following steps: (1) According to the chemical formula SrFe 11-2x Ti x Co x O 19 The following raw materials are weighed in stoichiometric proportions: strontium carbonate, ferric oxide, cobalt oxide, and titanium dioxide, where the value of x ranges from 0.3 to 0.9. (2) First grinding: Mix the above-weighed raw materials and grind them thoroughly to obtain a mixture for later use; (3) Pre-firing: The above mixture is pre-firing at 800-1000℃ for 1-3 hours to obtain pre-fired material; (4) Secondary grinding: After taking out the pre-burned material, grind and crush it to obtain grinding powder for later use; (5) Pressing and molding: Press the above-mentioned grinding powder into a pressed blank for later use; (6) Final firing: The pressed billet is fired at 1200-1350℃ for 1-3 hours to obtain the fired material for later use; (7) Crushing: The above-mentioned calcined material is placed in a crusher and crushed into powder to obtain the microwave absorbing material.

[0009] Preferably, the grinding time in step (2) is 0.5-2 hours.

[0010] Preferably, in step (3), the mixture is first loaded into an alumina crucible and then placed in a muffle furnace for pre-firing.

[0011] Preferably, the pressing pressure in step (5) is 20-40 MPa.

[0012] Preferably, the final firing temperature in step (6) is 1280°C and the final firing time is 2 hours.

[0013] This invention provides a titanium-cobalt doped M-type strontium ferrite microwave absorbing material and its preparation method, which has the following advantages compared with the prior art: (1) This invention utilizes Ti 4+ and Co 2+ ion pairs Fe 3+ Co-doping with Co-Ti ions effectively reduced the coercivity (Hc) and saturation magnetization (Ms) of M-type strontium ferrite. As the Co-Ti ion doping concentration (x) increased from 0 to 0.9, the coercivity decreased from 2663 Oe to 1402 Oe (a decrease of 47.4%), and the saturation magnetization decreased from 53.5 emu / g to 17.9 emu / g (a decrease of 66.5%). This reduction in coercivity and saturation magnetization improves the impedance matching characteristics of the material, allowing electromagnetic waves to penetrate the material more effectively and be absorbed and lost. (2) The titanium cobalt doped M-type strontium ferrite absorbing material prepared by the present invention has excellent broadband absorption performance. When x=0.3 and the thickness is 2.5mm, the minimum reflection loss (RL_min) reaches -33.4dB and the effective absorption bandwidth (RL<-10dB) reaches 8.9GHz; when the thickness is 2.0mm, the minimum reflection loss is -27.3dB and the effective absorption bandwidth is 8.5GHz, which meets the standard for large-scale use. (3) The material of the present invention exhibits good wave absorption performance in a wide thickness range (1.5 to 2.5 mm), and as the thickness increases, the peak reflection loss moves towards the low frequency direction, and the effective absorption bandwidth gradually increases. The matching thickness can be flexibly adjusted according to the actual application requirements. (4) The present invention is prepared by solid-phase reaction method. The process is simple (only seven steps are required: weighing → grinding → pre-calcination → secondary grinding → pressing → final calcination → crushing). It does not require the use of toxic organic solvents, nor does it require complicated pH adjustment and gelation process. It is easy to operate, has a short cycle and low cost, and is suitable for large-scale industrial production. (5) The present invention uses Ti and Co as doping elements, both of which are common transition metal elements. They are widely available and their prices are much lower than those of rare earth elements, which is conducive to reducing production costs and promoting their application. Attached Figure Description

[0014] Figure 1 This is a schematic diagram of phase analysis of various samples using an X-ray diffractometer in an embodiment of the present invention; Figure 2 These are SEM images of various samples in the embodiments of the present invention, wherein (a) is SrFe 11 O 19 SEM images, (b) showing SrFe 10.4 Ti 0.3 Co 0.3 O 19 SEM images, (c) showing SrFe 9.8 Ti 0.6 Co 0.6 O 19 SEM image, (d) is SrFe 9.2 Ti 0.9 Co 0.9 O 19 SEM image; Figure 3 SrFe prepared in Example 1 of this invention 10.4 Ti 0.3 Co 0.3 O 19Schematic diagram of EDS elemental surface scan analysis of the sample, where (a) is an electron microscope image, (b) is the Ti elemental distribution map, (c) is the Co elemental distribution map, (d) is the Sr elemental distribution map, (e) is the Fe elemental distribution map, and (f) is the O elemental distribution map; Figure 4 These are hysteresis loop diagrams of various samples in the embodiments of the present invention; Figure 5 For each sample in the embodiments of the present invention , , , A schematic diagram illustrating the changes; Figure 6 The diagram shows the absorption performance of samples with different thicknesses in the embodiments of the present invention, where (a) is a sample with a thickness of 1.0 mm; (b) is a sample with a thickness of 1.5 mm; (c) is a sample with a thickness of 2.0 mm; and (d) is a sample with a thickness of 2.5 mm. Detailed Implementation

[0015] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] Example 1: Preparation of SrFe 10.4 Ti 0.3 Co 0.3 O 19 Titanium-cobalt doped M-type strontium ferrite microwave absorbing material (x=0.3): (1) According to the chemical formula SrFe 10.4 Ti 0.3 Co 0.3 O 19 Strontium carbonate (SrCO3, purity >99%), ferric oxide (Fe2O3, purity >99.9%), cobalt oxide (Co2O3, purity >99%) and titanium dioxide (TiO2, purity >99%) were weighed out according to the stoichiometric ratio as raw materials. (2) Place the weighed raw materials in a mortar and grind them thoroughly for 1 hour; (3) The ground mixture is placed in an alumina crucible and preheated in a muffle furnace at 900°C for 2 hours; (4) Take out the pre-calcined product and grind it thoroughly again; (5) Press the ground powder into a cylindrical shape under a pressure of 30 MPa; (6) Place the cylindrical sample in a muffle furnace and calcine it at 1280°C for 2 hours; (7) The sample after final burning is put into a crusher and crushed into powder to obtain the microwave absorbing material.

[0017] Example 2: Preparation of SrFe 9.8 Ti 0.6 Co 0.6 O 19 The titanium-cobalt doped M-type strontium ferrite microwave absorbing material (x=0.6) was prepared using the same steps as in Example 1, except that in step (1), the chemical formula SrFe was used. 9.8 Ti 0.6 Co 0.6 O 19 Weigh each raw material according to the stoichiometric ratio.

[0018] Example 3: Preparation of SrFe 9.2 Ti 0.9 Co 0.9 O 19 The titanium-cobalt doped M-type strontium ferrite microwave absorbing material (x=0.9) was prepared using the same steps as in Example 1, except that in step (1), the chemical formula SrFe was used. 9.2 Ti 0.9 Co 0.9 O 19 Weigh each raw material according to the stoichiometric ratio.

[0019] Comparative Example 1: Preparation of SrFe 11 O 19 The undoped M-type strontium ferrite material (x=0) was prepared using the same steps as in Example 1, except that cobalt trioxide and titanium dioxide were not added in step (1), according to the chemical formula SrFe 11 O 19 Strontium carbonate and ferric oxide are weighed out according to their stoichiometric ratio.

[0020] Detection: 1. Test the microwave absorbing materials prepared in each of the above groups: (1) Phase analysis (XRD) Phase analysis of the samples was performed using an X-ray diffractometer (XRD, MacScience MPX18AHF). Test conditions: Cu-Kα radiation, scanning range 20°–70°.

[0021] Test results show (see) Figure 1The diffraction peak positions of all doped samples (x=0.3, 0.6, 0.9) are completely consistent with the standard diffraction peaks of pure M-type strontium ferrite (JCPDS card number 43-0002), and no other obvious impurity phase diffraction peaks are observed, indicating that most Ti 4+ Ions and Co 2+ The ions have entered the strontium ferrite lattice and replaced Fe. 3+ The ions formed a single-phase titanium-cobalt-doped strontium ferrite. A small amount of hematite phase (α-Fe2O3) diffraction peaks were observed in all samples, which is due to the small amount of Fe2O3 residue in the raw materials.

[0022] (2) Morphological observation (SEM) The particle morphology of the samples was observed using a field emission scanning electron microscope (SEM, Hitachi S-400) (see [reference]). Figure 2 ).

[0023] Observations show that pure M-type strontium ferrite (x=0) exhibits a relatively regular hexagonal plate-like morphology; the doped ferrite particles show fine-grained growth and plate-like stacking with a small number of voids between particles, and most doped particles exhibit irregular shapes with relatively rounded edges. This irregular morphology is beneficial for increasing the multiple reflection and scattering paths of electromagnetic waves within the material, thereby enhancing the material's wave absorption performance. Co-Ti ion substitution alters the lattice parameters in the strontium ferrite crystal structure, which is the main reason for the irregular shape of the samples.

[0024] (3) Element distribution (EDS mapping) Energy-dispersive X-ray spectroscopy (EDS) elemental surface scanning analysis was performed on the surface of the sample (x=0.3) from Example 1 (see [link to example]). Figure 3 ,in Figure 3 (a) is an electron microscope image. Figure 3 (b) is a distribution map of Ti elements. Figure 3 (c) is a distribution map of Co element. Figure 3 (d) is the distribution map of Sr element. Figure 3 (e) is the distribution map of Fe element. Figure 3 (f) is a distribution diagram of element O.

[0025] The results showed that Ti and Co elements were uniformly distributed on the sample surface. Combined with XRD analysis results, this confirmed the presence of Ti. 4+ Ions and Co 2+ The ions have entered the strontium ferrite lattice and successfully replaced the Fe. 3+ ion.

[0026] (4) Magnetic property test (VSM) The magnetic properties of the samples were measured at room temperature using a vibrating sample magnetometer (VSM, LakeShore 7404) with an applied magnetic field ranging from -20 kOe to 20 kOe (see [reference]). Figure 4 Hysteresis loop diagram).

[0027] The results above show that as the Co-Ti ion doping amount x increases, the coercivity (Hc) decreases from 2663 Oe when x=0 to 1402 Oe when x=0.9, a decrease of 47.4%; the remanent magnetization (Mr) decreases from 29.4 emu / g to 7.9 emu / g; and the saturation magnetization (Ms) decreases from 53.5 emu / g to 17.9 emu / g.

[0028] The main reason for the decrease in saturation magnetization is that Ti has a zero magnetic moment. 4+ Ions and Co with smaller magnetic moments 2+ Ions (3 μB) replaced Fe with a larger magnetic moment 3+ The presence of ions (5 μB) leads to a decrease in the net magnetic moment per unit volume of the material. The decrease in coercivity is due to the presence of 24 Fe atoms in the M-type strontium ferrite. 3+ They occupy five lattice positions: 2a, 4f2, 12k, 2b, and 4f1, with the 4f2 position having a significant impact on magnetocrystalline anisotropy. Co 2+ Preferentially replaces Fe at the 4f2 position 3+ Ions reduce the magnetocrystalline anisotropy of strontium ferrite, thereby reducing its coercivity.

[0029] (5) Electromagnetic parameter testing The samples from Examples 1-3 and Comparative Example 1 were mixed with paraffin at a mass ratio of 4:1 and pressed into coaxial ring samples with an inner diameter of 3 mm and an outer diameter of 7 mm under a pressure of 5 MPa. The complex permittivity of the samples was measured using a vector network analyzer (VNA, Ceyear 3656D) in the frequency range of 7–18 GHz via the transmission / reflection method. = +j ) and complex permeability ( = +j (See) Figure 5 ).

[0030] The real parts of the complex permittivity and complex permeability ( , The imaginary part () represents the material's ability to store electrical and magnetic energy. , This represents the material's ability to absorb electrical and magnetic energy.

[0031] Depend on Figure 5 It can be known that: With increasing frequency, the real part of the complex permittivity of the undoped sample (x=0) remains essentially unchanged, while the real part of the complex permittivity of the doped samples (x=0.3, 0.6, 0.9) shows a decreasing trend at high frequencies. This is due to the Ti introduced by doping. 4+ and Co 2+ This leads to lattice distortion, which enhances ionic and interfacial polarization relaxation, resulting in hysteresis in polarization response at high frequencies.

[0032] The imaginary part of the complex permittivity gradually increases with frequency, reflecting the intensification of polarization relaxation loss and conductivity loss with increasing frequency.

[0033] As x increases, the imaginary part of the complex permittivity and the imaginary part of the complex permeability both show an increasing trend, indicating that Ti-Co co-doping effectively enhances the dielectric loss and magnetic loss capability of the material.

[0034] (6) Wave absorption performance test According to transmission line theory, the reflection loss RL (dB) of a material is calculated using the following formula: Among them, Z in Z0 is the input impedance of the absorbing material surface, Z0 is the air impedance (377Ω), and ε r Let μ be the complex permittivity of the absorbing material. r Let be the complex permeability of the absorbing material, and c be the speed of light (3 × 10⁻⁶). 8 (m / s), f is the electromagnetic wave frequency, and d is the thickness of the absorbing material.

[0035] Based on the above formula, the reflection loss curves of the samples from Examples 1-3 and Comparative Example 1 at different thicknesses (1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm) were calculated (see [reference]). Figure 6 ).

[0036] Typically, RL < -10dB indicates that the material can absorb more than 90% of the incident electromagnetic waves. This frequency range is called the effective absorption bandwidth, which is a key indicator for evaluating the performance of microwave absorbing materials.

[0037] Depend on Figure 6 It can be known that: When the thickness is 1.0mm ( Figure 6 a): All samples exhibited poor absorption performance with an extremely narrow effective absorption bandwidth.

[0038] When the thickness is 1.5mm ( Figure 6b): Sample 1 (x=0.3) exhibits good absorption performance: minimum reflection loss is -20.6dB, and effective absorption bandwidth is 5.8GHz (covering the entire Ku band from 12 to 18GHz).

[0039] When the thickness is 2.0mm ( Figure 6 c): The minimum reflection loss of the sample in Example 1 (x=0.3) reached -27.3dB, and the effective absorption bandwidth reached 8.5GHz, which met the standard for large-scale practical application.

[0040] When the thickness is 2.5mm ( Figure 6 d): The sample in Example 1 (x=0.3) has the best absorption performance: the minimum reflection loss reaches -33.4dB and the effective absorption bandwidth reaches 8.9GHz.

[0041] The samples of Example 2 (x=0.6) and Example 3 (x=0.9) also showed some absorption performance, but overall they were not as good as the sample of Example 1 (x=0.3). The undoped sample of Comparative Example 1 (x=0) had the worst absorption performance.

[0042] As the sample thickness increases, the frequency corresponding to the peak reflection loss shifts to lower frequencies, and the effective absorption bandwidth gradually increases, conforming to the quarter-wavelength matching model.

[0043] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A titanium-cobalt-doped M-type strontium ferrite microwave absorbing material, characterized in that, The microwave absorbing material has the general chemical formula SrFe. 11-2x Ti x Co x O 19 , where x takes values ​​ranging from 0.3 to 0.

9.

2. The microwave absorbing material according to claim 1, characterized in that: The value of x can be any one of 0.3, 0.6 or 0.

9.

3. A method for preparing the microwave absorbing material as described in claim 1, characterized in that, The preparation method includes the following steps: (1) According to the chemical formula SrFe 11-2x Ti x Co x O 19 The following raw materials are weighed in stoichiometric proportions: strontium carbonate, ferric oxide, cobalt oxide, and titanium dioxide, where the value of x ranges from 0.3 to 0.

9. (2) First grinding: Mix the above-weighed raw materials and grind them thoroughly to obtain a mixture for later use; (3) Pre-firing: The above mixture is pre-firing at 800-1000℃ for 1-3 hours to obtain pre-fired material; (4) Secondary grinding: After taking out the pre-burned material, grind and crush it to obtain grinding powder for later use; (5) Pressing and molding: Press the above-mentioned grinding powder into a pressed blank for later use; (6) Final firing: The pressed billet is fired at 1200-1350℃ for 1-3 hours to obtain the fired material for later use; (7) Crushing: The above-mentioned calcined material is placed in a crusher and crushed into powder to obtain the microwave absorbing material.

4. The preparation method according to claim 3, characterized in that: The grinding time in step (2) is 0.5-2 hours.

5. The preparation method according to claim 3, characterized in that: In step (3), the mixture is first loaded into an alumina crucible and then placed in a muffle furnace for pre-firing.

6. The preparation method according to claim 3, characterized in that: The pressing pressure in step (5) is 20-40 MPa.

7. The preparation method according to claim 3, characterized in that: In step (6), the final firing temperature is 1280℃ and the final firing time is 2h.